Maximal exercise studies in Scottish athletes. Issue 2 (June 1976) - Leitch, A. G.; Clancy, L.
Abstract : We have studied maximal oxygen uptake, maximal heart rate, maximal exercise ventilation and the ventilatory response to exercise in 24 male and 14 female Scottish athletes. The values for maximal oxygen uptake are similar to those reported in other international studies. In eight athletes repeat measurements of maximal oxygen uptake 7-11 months after the initial study showed no change from the initial values. The values for the ventilatory response to exercise in our athletes were normal. The relationship is discussed between maximal oxygen uptake and ventilatory responses to exercise, hypoxia and hypercapnia and it is suggested that these may be related to athletic event.